Didatização dos gêneros: análise procedimental das sequências didáticas em trabalhos realizados por graduandos em língua portuguesa a partir do ano de 2018, do campus da UFPA de Abaetetuba-PA - LIMA, Aldeneide Barbosa de (2022)
The present work brings as a discussion the didactization of genres from the procedural analysis of the didactic sequences, seeking to ascertain how the content of the didactization of genres is presented in the works carried out by undergraduate students in Letters - Portuguese Language, from the Campus of Abaetetuba, from of the year 2018. There were 5 works analyzed from the perspective of the importance of working with the didacticization of genres from procedural knowledge, from a didactic sequence, as a methodological tool that can contribute to the development of the teaching of the mother tongue. In this way, the magnitude of this research is justified, insofar as it can collaborate so that the work with genres in basic education can be carried out by future professionals of the Portuguese Language, in a very didactic way, which takes into account tools such as the procedural knowledge so that the didactic sequence is applied efficiently. The methodological procedures are presented as applied, bibliographic research, with a qualitative approach, with data collection procedure in documentary research, such as documents written by undergraduate students in Letters - Portuguese Language, which were produced between 2018 to 2019. In these works, the authors develop a didactic sequence according to the assumptions of Dolz, Schneuwly and Noverraz (2004), following the following steps: Preparatory Activities, Situation Presentation, Initial Production, Modules and Final Presentation. After analyzing the work carried out, we realized that the authors followed the didacticization of the genres through the didactic sequence, which provided an organization in teaching, which motivated students to understand the content of the proposed genre, perform the tasks, and stimulate the learning of a significant way. And, above all, the didactic sequence strategies presented in the 5 researches, we observed that they are proposals that fit the new guidelines of the pedagogical process proposed by the BNCC - National Common Curricular Base, which allows us to understand that the didactic sequences are positive for literacy in basic education.